THE DESTINATION IMAGE OF BUCOVINA AMONG ROMANIAN TOURISTS - Ariadna Ioana JURAVLE (GAVRA); Constantin SASU; Loredana TEREC-VLAD (Cross-Cultural Management Journal, 2016)

(untitled)
The aim of this article is to identify the destination image of Bucovina among Romanian tourists. Bucovina is one of the most important tourist destinations of Romania, it is located in the North Eastern region of Romania and tourism has the potential to provide significant support for economic development of this region. This economic development may occur if the elements of tourism are well-managed. One of the factors influencing the success of a destination is its image. Earlier studies showed the importance of destination image, even though no studies have been conducted for Bucovina to identify the image of this destination. To implement this study, we used survey as the research method and the questionnaire as our research tool. We conducted the content analysis of responses to open questions. The items were included into a broader questionnaire although this article comprises just the qualitative research in which we included emergent coding.